Potential Therapeutic Strategies for Renal Fibrosis: Cordyceps and Related Products - Tan, Wei; Wang, Yunyan; Dai, Hongmei; Deng, Junhui; Wu, Zhifen; Lin, Lirong; Yang, Jurong (Frontiers in Pharmacology, 2022)
At present, no effective drug exists for the treatment of renal fibrosis, and it is particularly important to find safe and effective treatment for renal fibrosis. Cordyceps has several medical effects, including immunoregulatory, antitumor, anti-inflammatory, and antioxidant effects, and may prevent kidney, liver, and heart disease. Cordyceps has also been reported to be effective in the treatment of renal fibrosis. The present article reviews the potential mechanisms of Cordyceps against renal fibrosis, focusing on the effects of Cordyceps on inflammation, oxidative stress, apoptosis, regulation of autophagy, reduction of extracellular matrix deposition, and fibroblast activation. We also discuss relevant published clinical trials and meta-analyses, and the compounded formulation of Cordyceps may have an antifibrotic effect. Available clinical studies support the possibility that Cordyceps and related products provide benefits to patients with chronic kidney diseases as adjuvants to conventional drugs. However, the existing clinical studies are limited by low quality and significant heterogeneity. The use of Cordyceps and related products may be a potential strategy for the treatment of renal fibrosis. Randomized controlled trial studies with good methodological quality, favorable experimental design, and large sample size are needed to evaluate the efficacy and safety of Cordyceps.